2020
DOI: 10.3390/cancers12113155
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Functional MRI and PET/MRI in Multiple Myeloma

Abstract: Bone disease is one of the major features of multiple myeloma (MM), and imaging has a pivotal role in both diagnosis and follow-up. Whole-body magnetic resonance imaging (MRI) is recognized as the gold standard for the detection of bone marrow involvement, owing to its high sensitivity. The use of functional MRI sequences further improved the performances of whole-body MRI in the setting of MM. Whole-body diffusion-weighted (DW) MRI is the most attractive functional technique and its systematic implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…In the present study, the MRI protocols mainly used conventional T1 weighted image (T1WI), T2 weighted image (T2WI), short TI inversion recovery (STIR), and contrast enhanced T1WI. However, a good diagnostic value of whole-body diffusion-weighted image (WBDWI) or PET/MRI has been reported in the treatment assessment of patients with MM [ 30 , 32 , 33 , 34 , 35 ]. The Myeloma Response Assessment and Diagnosis System (or MY-RADS) [ 16 ], a standardized evaluation method proposed in 2019, also recommends WBDWI according to its usefulness in previous reports [ 32 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the MRI protocols mainly used conventional T1 weighted image (T1WI), T2 weighted image (T2WI), short TI inversion recovery (STIR), and contrast enhanced T1WI. However, a good diagnostic value of whole-body diffusion-weighted image (WBDWI) or PET/MRI has been reported in the treatment assessment of patients with MM [ 30 , 32 , 33 , 34 , 35 ]. The Myeloma Response Assessment and Diagnosis System (or MY-RADS) [ 16 ], a standardized evaluation method proposed in 2019, also recommends WBDWI according to its usefulness in previous reports [ 32 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Larger standardized prospective studies are, however, warranted to confirm these results. Additionally, the complementary role of 18 F-FDG PET/CT and DW-MRI should be further addressed, for example through studies performed on PET/MRI hybrid systems (75).…”
Section: F-fdg Pet/ct Compared With Diffusion-weighted Mri After Asctmentioning
confidence: 99%
“…A systematic review concluded that data on this topic are too heterogeneous, with biased accrual and lack of independent reference standard, which also precluded performing a meta-analysis [125]. Hence, it remains unclear which modality may be best suited for response assessment and the evaluation of both techniques using either side-by-side or on PET/MRI hybrid scanners should provide information on their respective effectiveness [126] (Figs. 5,6,10).…”
Section: Comparisons Of Pet and Mri And Value Of The Pet/ Mri Technologymentioning
confidence: 99%
“…5,6,10). PET/MRI indeed combines the two most effective imaging modalities in MM and allows a one-step exhaustive evaluation and comparison between both techniques at diagnosis, at the time of response assessment and MRD detection [99,126].…”
Section: Comparisons Of Pet and Mri And Value Of The Pet/ Mri Technologymentioning
confidence: 99%